The Effect of Working Capital Management on the Profitability of Firms: An Inter-Industry Analysis. - Saha, Deeposhree (2013)
The manufacturing sector is one of the important business sectors of the United Kingdom. This study is designed to compare the Profitability and Working Capital position of four different manufacturing industries namely the Pharmaceutical Industry, the Food Industry, the Chemical Industry and the Electronic and Electrical equipment Industry. To see to what extent the working capital management affects the profitability- 96 firms across the four industries for a time span of four years (2009-2012 were chosen. Ratio Analysis, Correlation Matrix and Panel Data Regression Analysis have been used to show correlation between Profitability and Working Capital position of firms and the impact of the working capital components and profitability. For the source of data, the study relied on financial statements of the companies. It is observed from the study that profitability and Working Capital Management position of the Electronic industry and the Pharmaceutical were not that satisfactory. However, the findings for the Food and Chemical industry show results consistent to the findings of the previous literature. The study reveals that correlation exists between Working Capital Management and Profitability. The study tries to carry out an inter-industry analysis, where the results of the different industries of the manufacturing sector are compared and contrasted to learn what impact working capital management has on profitability.